2019
DOI: 10.5114/fn.2019.86294
|View full text |Cite
|
Sign up to set email alerts
|

Theta burst stimulation influence the expression of BDNF in the spinal cord on the experimental autoimmune encephalomyelitis

Abstract: Repetitive transcranial magnetic stimulation (rTMS) induces changes in expression of proteins engaged in the activity of excitatory and inhibitory systems, restores these functions and suppresses the progression of disability in experimental autoimmune encephalitis (EAE). The structural type of TMS, the arrangement as theta burst stimulation (TBS) has been applied as intermittent TBS (iTBS) and continuous TBS (cTBS) protocols to female adult DA rats. The animals were randomly divided into experimental groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…DiscussionSubtle pathological changes occur in the brain or spinal cord of rats immunized for EAE before the onset of EAE signs. Astrogliosis has been reported as an underlying mechanism of EAE[12]. Gliosis is usually established after two to three weeks of a CNS injury in rats, which coincided with our results that the peak of the EAE clinical score was achieved at 14dpi and overlapped with the highpoint of ONS measured in the spinal cord of treated rats ([30]).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…DiscussionSubtle pathological changes occur in the brain or spinal cord of rats immunized for EAE before the onset of EAE signs. Astrogliosis has been reported as an underlying mechanism of EAE[12]. Gliosis is usually established after two to three weeks of a CNS injury in rats, which coincided with our results that the peak of the EAE clinical score was achieved at 14dpi and overlapped with the highpoint of ONS measured in the spinal cord of treated rats ([30]).…”
supporting
confidence: 91%
“…It has been shown that repetitive transcranial stimulation arouses remyelination and fosters the expression of neurotrophic factors that are of significant importance for neuro-regeneration in EAE animals [12]. In the cerebral cortex, it may promote neuronal activities in remote zones of the spinal cord, which is interconnected with the main motor pathway -corticospinal tract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood removal from minimizes interferences for immunostaining of microscopic preparations [19]. The assessed experimental outcomes referred to iTBS and cTBS impact on the astroglial glutamate transporters capacity in EAE rats model.…”
Section: Methods 21 Animals and Experimental Proceduresmentioning
confidence: 99%
“…Decapitation was performed 24 hours after the last TBS treatment. Prior decapitation, all animals were intraperitoneally anesthetized with sodium pentobarbital [19].…”
Section: Methods 21 Animals and Experimental Proceduresmentioning
confidence: 99%